Physics Learning through Active Learning Based Interactive Conceptual Instructions (ALBICI) to Improve Critical Thinking Ability - Diani, Rahma; Irwandani, Irwandani; Al-Hijrah, Al-Hijrah; Yetri, Yetri; Fujiani, Dwi; Hartati, Niken Sri; Umam, Rofiqul (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2019)
The process of physics learning in MAN (Islamic senior high school) 2 Bandar Lampung which is still teacher-centered causes students to have low critical thinking skills. One learning model that can be used to overcome this problem is the Active Learning Based Interactive Conceptual Instructions (ALBICI) model which is equipped with Predict, Discuss, Explain, Observe, Discuss, Explore, Explain Tasks (PDEODE*E tasks). The purpose of this study is to determine the effectiveness of the ALBICI model with PDEODE*E tasks in improving students’ critical thinking skills on momentum and impulses subject material. The type of research used is quasi-experimental with 30 students of the class X1 as the experimental class and 30 students of class X2 as the control class. The results of data analysis using t-test at a significance level of 0.05 indicate that the ALBICI model with PDEODE*E tasks iseffective in improving students’ critical thinking skills. Furthermore, theobtainedeffect size of 0.6 indicates that the model's effectiveness falls into the medium category.